(untitled) (Journal of Asian Development Studies, 2023)
This research investigates the landscape of artificial intelligence (AI) integration in Pakistani journalism, exploring perceived benefits, challenges, ethical considerations, and the overall outlook on this transformative process. Drawing on interviews with industry professionals, the study contributes theoretical insights to the Diffusion of Innovations theory, unveiling varying degrees of AI integration awareness and perspectives within the Pakistani news industry. A human-centric ethical perspective is introduced, emphasizing concerns about job displacement and the evolving role of journalists. The delicate balance between AI’s efficiency gains and ethical considerations is explored, with practical implications highlighting the need for targeted education, transparent communication, and cost-effective solutions to overcome barriers and foster widespread AI adoption. The research underscores the significance of continuous adaptation to technological advancements for seamless integration. As Pakistan cautiously navigates the AI landscape in news production, this study lays the groundwork for theoretical frameworks and practical strategies, providing valuable insights for the ethical, efficient, and responsible integration of AI technologies.